Vapour–liquid equilibria in the system methanethiol–water. (September 2021) - Jou, F.-Y.; Mather, A.E.; Schubert, C.N.; Schmidt, K.A.G.
Highlights: The solubility of methanethiol in water was measured. The data were correlated with the Peng-Robinson equation of state. Henry's law constants were correlated with temperature. Abstract: The solubility of methanethiol in water was measured at temperatures in the range (298–413) K at pressures up to 1.1 MPa. The literature and the new data were correlated with the Peng-Robinson equation of state. Henry's law constants, from the literature and from the Peng-Robinson equation of state were correlated with temperature over a temperature range of 273.15 K–588.7 K.